Early Childhood Speaking Skills Through the Media of Paper Puppets Based on Fables - Kencana, Rita; Yusnita, Yusnita; Thalia, Karinda Dwi (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to stimulate early childhood speaking skills through the use of paper puppet media based on fabled fairy tales. The subjects of this study are teachers, and students aged 5-6 years of KB Al-Adawiyah Tembilahan. The research method uses a qualitative approach with observation, interview, and documentation data collection techniques. The results of the study show that the use of paper puppets based on fables can stimulate speaking skills. Children are very enthusiastic about learning and pay attention to what the teacher is saying, can speak in simple words in their entirety, enjoy listening and retelling simple stories in order and easy to understand, understand the form of questions by using what, why, and how, can use prepositions: inside, outside, above, below, on the side, can participate in a conversation and do not dominate to always want to be heard. This is proven through the participation of children in retelling the stories conveyed as well as their ability to express ideas and emotions and actively participate in learning with the guidance of teachers. This study suggests that the media applied should be more varied as a way to stimulate early childhood speaking skills.